The discovery of rest-frame UV colour gradients and a diversity of dust morphologies in bright z ≃ 7 Lyman-break galaxies. Issue 4 (24th December 2021) - Bowler, R A A; Cullen, F; McLure, R J; Dunlop, J S; Avison, A
ABSTRACT: We present deep ALMA dust continuum observations for a sample of luminous ( M UV < −22) star-forming galaxies at z ≃ 7. We detect five of the six sources in the far-infrared (FIR), providing key constraints on the obscured star formation rate (SFR) and the infrared-excess-β (IRX–β) relation without the need for stacking. Despite the galaxies showing blue rest-frame ultraviolet (UV) slopes (β ≃ −2) we find that 35–75 per cent of the total SFR is obscured. We find the IRX–β relation derived for these z ≃ 7 sources is consistent with that found for local starburst galaxies. Using our relatively high-resolution (FWHM 0.7 arcsec ) observations we identify a diversity of dust morphologies in the sample. We find both compact emission that appears offset relative to the unobscured components and extended dust emission that is co-spatial with the rest-frame UV light. In the majority of the sources, we detect strong rest-frame UV colour gradients (with up to Δβ ≃ 0.7–1.4) as probed by the multiband UltraVISTA ground-based data. The observed redder colours are spatially correlated with the location of the FIR detection. Our results show that even in bright Lyman-break galaxies at z ≃ 7 the peak of the star formation is typically hosted by the fainter, redder, regions in the rest-frame UV, which have an obscured fraction of f obs ≥ 0.8. As well as demonstrating the importance of dust obscured star formation within the Epoch of Reionization, these observations provide an exciting taster of the rich spatially resolved data sets that will be obtained from JWST and high-resolution ALMA follow-up at these redshifts.